Doctor shopping behaviour and its determinants among people with chronic diseases in rural Kancheepuram district, Tamil Nadu: a cross-sectional study - Tharumaraj, Muthukumar; Annadurai, Kalaivani; Cinthiya, Jerrin; Ranganathan, Karnaboopathy (International Journal Of Community Medicine And Public Health, 2019)
Background: Doctor shopping is defined as the practice of patient seeking multiple health care providers without making efforts to coordinate care or informing physicians of the multiple care givers for the same illness or to procure prescription drugs illicitly. This study was planned to explore the doctor shopping behaviour and its determinants among people with chronic diseases in rural Kancheepuram district, Tamil Nadu. Methods: A cross sectional study was conducted among patients of chronic diseases residing in Sembakkam village, Kancheepuram District, Tamil Nadu. Data was collected using a pre-tested semi-structured schedule adopted from Agarwal et al will be used. Results: Prevalence of doctor shopping was found to be 73.7% among the study population which is visiting more than one doctor for the same diagnosis. The main reason given by the participants for consulting more than one doctor was consistence of the symptoms (34%) followed by location of the health facility (15.9%) and non-acceptance of the diagnosis (15.5%). Conclusions: Patient education, good interpersonal communication skills, and health system strengthening measures can increase responsiveness of the community toward the health systems and thereby reduce doctor shopping behaviour.